Intryga audio. Hybrydyczna rzeczywistość słuchowiska Krzysztofa Czeczota Andy - Łastowiecki, Janusz (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2015)
The concept of the simulacrum creatively influenced reflections on postmodernism. In this text it will help us to see the phenomenon of the hybridization of meaning constituted in a dolby surround radio drama. Czeczot’s drama Andy uses the convention of noir to illustrate problems associated with media coverage. The article demonstrates the role of the listener in the formula created by the drama’s author, that of surround sound.